Subcutaneous filariasis: An unusual presentation with an adult gravid worm on aspiration - Nanda, Annu (Trop Parasitol, 2018)
Detection of adult gravid filarial worm in fine-needle aspiration cytology (FNAC) smears is unusual despite the high incidence of this parasite in endemic zones. Bancroftian filariasis presenting as subcutaneous nodules is very rare, and only a few cases are reported in literature. In spite of various reports stating the presence of microfilaria using aspiration cytology in various sites, the presence of an adult gravid filarial worm in subcutaneous nodules by FNAC is an extremely rare finding. We hereby report an unusual case of detection of adult gravid worm of Wuchereria bancrofti on FNAC of a subcutaneous nodule in the axilla. In differential diagnosis of subcutaneous nodular swellings, a possibility of filariasis must be kept in mind, and a careful search should be done for the adult worm or microfilaria in the aspiration smears done for an accurate diagnosis. The conventional method of diagnosis of filariasis is by demonstration of microfilaria in the peripheral blood smear which may be diurnal or nocturnal. Buffy coat can be helpful in detecting microfilaria in asymptomatic cases with peripheral blood eosinophilia.